2022
DOI: 10.1016/j.jsxm.2022.03.469
|View full text |Cite
|
Sign up to set email alerts
|

210 The Effect of Antioxidant Supplementation on Operated or Non-Operated Varicocele-Associated Infertility: A Systematic Review and Meta-Analysis

Abstract: Introduction In patients with varicocele-associated infertility, the effect of antioxidant supplementation on fertility is unknown. Objectives To perform a systematic review and meta-analysis exploring the role of antioxidant supplementation in patients with operated or non-operated varicocele. Methods We searched PubMed, Cochrane Library, Web of Science and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…However, one-third of the respondents felt that there was no need to rush into VR and that patients may benefit from an initial trial with medical management before considering surgery. This is in concordance with a recent meta-analysis which suggested that while antioxidants (AOX) did not improve pregnancy rates in men who had VR, AOX may be of benefit in men with unoperated varicoceles [19]. Giving a couple time to conceive naturally without rushing into VR, especially if they are young, is supported by a study that showed similar pregnancy rates between conservative and surgical approaches when the duration of infertility was short, but greater chances of pregnancy after VR if the couple has been infertile for more than 2 years [20].…”
Section: (3) Discussionsupporting
confidence: 91%
“…However, one-third of the respondents felt that there was no need to rush into VR and that patients may benefit from an initial trial with medical management before considering surgery. This is in concordance with a recent meta-analysis which suggested that while antioxidants (AOX) did not improve pregnancy rates in men who had VR, AOX may be of benefit in men with unoperated varicoceles [19]. Giving a couple time to conceive naturally without rushing into VR, especially if they are young, is supported by a study that showed similar pregnancy rates between conservative and surgical approaches when the duration of infertility was short, but greater chances of pregnancy after VR if the couple has been infertile for more than 2 years [20].…”
Section: (3) Discussionsupporting
confidence: 91%
“…While a varicocelectomy can improve sperm motility, other sperm parameters are still controversial [30][31][32][33]. Adjuvant therapy using antioxidant supplements to improve sperm quality [34,35] has had conflicting outcomes [36].…”
Section: Varicocelementioning
confidence: 99%
“…On the other hand, the use of antioxidants in men with infertility and VCL who have not undergone surgical repair has recently been in the focus of interest, although the existing evidence is scarce and conflicting (Busetto et al, 2018; Cavallini et al, 2004; Festa et al, 2014; Gual‐Frau et al, 2015; Oliva et al, 2009; Pyrgidis et al, 2021; Sofimajidpour et al, 2016).…”
Section: Introductionmentioning
confidence: 99%